Controlled synthesis of spinous gold nanoparticles and their use for surface-enhanced Raman scattering (SERS) detection of the antibiotic sulfathiazole. (21st March 2023) - Vo, Khuong Quoc; Tran, Man Van; Nguyen, Thu Anh; Tran Cao, Anh-Thi; Vu, Sy Van; Tran, Kha Ni; Si, Nguyen Thanh; Pham, Vu-Nhat
Abstract : Spinous nanostructures with long tips could improve the SERS detection of sulfathiazole by creating more hot spots in the vicinity of particles. Abstract : Sulfathiazole is an antibiotic used to prevent diseases and promote animal growth, and may pose health risks to humans when consumed excessively. Herein, we prepared a nanosubstrate for trace determination using the surface-enhanced Raman scattering (SERS) technique by synthesizing spinous gold nanoparticles (SGNPs) through a rapid and straightforward seed-mediated method. Prior to detection, SGNPs with long tips were effectively synthesized by varying the seed solutions and the volume of ascorbic acid. These spinous nanostructures with long tips could improve the SERS detection of sulfathiazole (STZ) by creating more hot spots in the vicinity of particles. Furthermore, the SERS nano-substrate is facile to prepare with high sensitivity, and the testing sample does not undergo a complicated pretreatment procedure. The results show that nano-substrates can detect STZ at low concentrations ranging from 0.01 to 50 μg mL −1, with an excellent linear correlation between the concentration and intensity ( R 2 = 0.99). The limit of detection (LOD) reaches 0.22 μg mL −1, and the limit of quantification is 0.73 μg mL −1 . In addition, the SERS nanosubstrate can exhibit good reproducibility with an RSD of 6.26%, as evaluated with STZ solution at a low concentration of 40 μg mL −1 . The assignments of STZ Raman bands were performed using density-functional theory (DFT) quantum chemical calculations. The strong interaction affinity between Au atoms and STZ compounds was also described by calculating the binding energy of isolated species and Au20 -STZ complexes. The STZ could be anchored on the Au surface through thiazole nitrogen. Furthermore, the calculated SERS spectrum of Au-STZ could be assigned to the experimental ones with the most enhanced signal near 1430 and 1540 cm −1 . Potential applications that benefit from this SERS nanosubstrate are measurements for a variety of antibiotics.